Rice Husk Derived Porous Silica as Support for Pd and CeO2 for Low Temperature Catalytic Methane Combustion - Dongjing Liu (Catalysts, 2019)
The separation of Pd and CeO2 on the inner surface of controlled porous glass (CPG, obtained from phase-separated borosilicate glass after extraction) yields long-term stable and highly active methane combustion catalysts. However, the limited availability of the CPG makes such catalysts highly expensive and limits their applicability. In this work, porous silica obtained from acid leached rice husks after calcination (RHS) was used as a sustainable, cheap and broadly available substitute for the above mentioned CPG. RHS-supported Pd-CeO2 with separated CeO2 clusters and Pd nanoparticles was fabricated via subsequent impregnation/calcination of molten cerium nitrate and different amounts of palladium nitrate solution. The Pd/CeO2/RHS catalysts were employed for the catalytic methane combustion in the temperature range of 150–500 °C under methane lean conditions (1000 ppm) in a simulated off-gas consisting of 9.0 vol% O2, and 5.5 vol% CO2 balanced with N2. Additionally, tests with 10.5 vol% H2O as co-feed were carried out. The results revealed that the RHS-supported catalysts reached the performance of the cost intensive benchmark catalyst based on CPG. The incorporation of Pd-CeO2 into RHS additionally improved water-resistance compared to solely Pd/CeO2 lowering the required temperature for methane combustion in presence of 10.5 vol% H2O to values significantly below 500 °C (T90 = 425 °C).